Efficacy and feasibility of G-POEM in management of patients with refractory gastroparesis: a systematic review and meta-analysis - Aghaie Meybodi, Mohamad; Qumseya, Bashar J.; Shakoor, Delaram; Lobner, Katie; Vosoughi, Kia; Ichkhanian, Yervant; Khashab, Mouen A. (Endoscopy International Open, 2019)
Background and aim Clinical management of patients with gastroparesis is challenging. Prior pyloric targeted procedures are either invasive or have questionable long-term efficacy. Gastric per-oral endoscopic myotomy (G-POEM) has been recently introduced as a minimally invasive approach. In this review, we performed a meta-analysis to evaluate the feasibility and efficacy of this technique in the management of patients with refractory gastroparesis.Methods PubMed, Embase, and Scopus databases were searched to identify relevant studies published through May 2018. Weighted pool rates (WPR) of the clinical resolution were calculated. Pooled values of Gastroparesis Cardinal Symptom Index (GCSI) before and after the procedure were compared. Pooled difference in means comparing gastric emptying before and after the procedure was calculated. Fixed or random effect model was used according to the level of heterogeneity.Results Seven studies with 196 patients were included in the meta-analysis. The mean value of procedure duration was 69.7 (95 % confidence interval [95 % CI]: 39 – 99 minutes) and average estimate of hospital stay was 1.96 (95 % CI: 1.22 – 2.95) days. The WPR for clinical success was 82 % (95 % CI: 74 % – 87 %, I2 = 0). Compared with pre-procedure GCSI values, mean values of GCSI were reduced significantly at 5 days (–1.57 (95 % CI:–2.2,-0.9), I2 = 80 %) (P < 0.001). Mean values of gastric emptying were significantly decreased 2 – 3 months after the procedure (–22.3 (95 %CI: –32.9, – 11.6), I2 = 67 %) (P < 0.05).Conclusion Due to the high rate of clinical success and low rate of adverse events, G-POEM should be considered in management of refractory gastroparesis.